2005
DOI: 10.1103/physrevlett.94.126601
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field Effect in Diluted Magnetic Insulator AnataseCo:TiO2

Abstract: An external electric field induced reversible modulation of room temperature magnetic moment is achieved in an epitaxial and insulating thin film of dilutely cobalt-doped anatase TiO 2 . This first demonstration of electric field effect in any oxide based diluted ferromagnet is realized in a high quality epitaxial heterostructure of PbZr 0.2 Ti 0.8 O 3 /Co:TiO 2 /SrRuO 3 grown on (001) LaAlO 3 . The observed effect, which is about 15% in strength in a given heterostructure, can be modulated over several cycles… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(61 citation statements)
references
References 35 publications
3
58
0
Order By: Relevance
“…Taking into consideration the highly insulating nature of ZnO, it seems to argue against the explanation of enhancement in magnetic ordering as a result of increased carrier concentration as shown by studies on bulk samples [39]. According to the widely used carrier-induced ferromagnetic mechanism [22,40], a large amount of free carriers and mobility are two important factors to get room temperature ferromagnetism. As recent studies reported, a ferromagnetic exchange mechanism which involves a spin-polarized electron trapped at an oxygen vacancy [41].…”
Section: Resultsmentioning
confidence: 92%
“…Taking into consideration the highly insulating nature of ZnO, it seems to argue against the explanation of enhancement in magnetic ordering as a result of increased carrier concentration as shown by studies on bulk samples [39]. According to the widely used carrier-induced ferromagnetic mechanism [22,40], a large amount of free carriers and mobility are two important factors to get room temperature ferromagnetism. As recent studies reported, a ferromagnetic exchange mechanism which involves a spin-polarized electron trapped at an oxygen vacancy [41].…”
Section: Resultsmentioning
confidence: 92%
“…Just because of the demand of practical spintronic applications, ferromagnetic DMSs with curie temperatures (T c ) greatly exceeding room temperature are required. In many reports, doping DMSs with transition metals (TM) showed an effective route to obtain room-temperature ferromagnetism, such as ZnO [3][4][5], TiO 2 [6][7][8], GaN [9,10] etc.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 The change of magnetization upon the application of an electric field was measured using a vibrating sample magnetometer in the direction of the biasing magnetic field. The MEC was electroded 16 as described before so that an electric field could be applied while the magnetization was determined.…”
mentioning
confidence: 99%